Analisis Kadar Kalium Pada Pisang Raja (Musa Paradisiaca) Dan Pisang Barangan (Musa Acuminata Linn) Yang Berasal Dari Kabupaten Pinrang - Rizman Naim (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2016)
A research on the analysis of the levels of potassium in plantain (Musa paradisiacal) and banana (Musa acuminata linn) for the purpose of determining the levels of potassium in plantain and banana which originated from the district Pinrang, the benefits of research as information for the public about the importance the role of potassium in the body. This is a descriptive study using Atomic Absorption Spectrophotometer (AAS) at a wavelength of 766.5 nm. From the results of aboratory analysis potass um levels each each sample P.raja1 = 121.27 mg / g. P raja2 = 131.03 mg / g, P.raja3 126.27 mg / g, P.barangan1105.39 ug /g P barangan2 104.87 mg/ g, P.barangan3 = 107.09 mg/g Plantains have higher levels of potassium than banana, while the general standard of potassium in bananas is 358 ug / g It is recommended to consumers to consume a banana as one type of fruit that contain potassium to meet the needs of potassium per day